Criminal Law: Text, Cases and Materials - Stuart Macdonald (Pearson, 2015)
This text, cases and materials book combines detailed commentary and analysis of the law with excerpts from a range of sources, both legal and non-legal, to help set the law in context and deepen your understanding of this core area of legal study.